Method for controlling high plasticity heterogeneous structure by metal asymmetric rolling coupled with recrystallization

By regulating the heterogeneous structure of Ti-Zr-Ta alloys through high-temperature asynchronous rolling and recrystallization annealing processes, the problem of achieving both strength and plasticity at room temperature is solved, and a synergistic improvement of high strength and high plasticity is achieved.

CN120571863BActive Publication Date: 2025-10-10NORTHEASTERN UNIV CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511094037.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-06
Publication Date
2025-10-10
Estimated Expiration
2045-08-06

AI Technical Summary

Technical Problem

Ti-Zr-Ta alloys are difficult to achieve both strength and plasticity at room temperature. Existing technologies make it difficult to effectively control their heterogeneous structures through asymmetric rolling, resulting in brittle fracture of the material during room temperature processing. The contradiction between strength and plasticity is difficult to resolve.

Method used

A high-temperature asynchronous rolling combined with recrystallization annealing process is adopted. By designing the upper and lower roll speed ratio to be 2~4, multi-pass differential rolling is performed, and the temperature is kept at 890℃~910℃ for 100s~120s. The volume fraction of the annealing recrystallization area is controlled to 50%~80% to form a heterogeneous structure.

Benefits of technology

The room temperature plasticity of Ti-Zr-Ta alloys is significantly improved, and the elongation is increased by more than 2 times while maintaining high strength. This solves the contradiction between strength and plasticity in traditional methods and is easy and efficient to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120571863B_ABST
    Figure CN120571863B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of metal material processing, and discloses a method for regulating high plasticity heterogeneous structure by metal asymmetric rolling coupling recrystallization. The as-cast Ti-Zr-Ta series alloy is firstly heated to 890-910 DEG C and kept for 1-2 hours. The as-cast Ti-Zr-Ta series alloy after keeping is subjected to multi-pass differential rolling by an asynchronous rolling mill, and then is subjected to primary quenching after differential rolling to obtain a rolled Ti-Zr-Ta series alloy. The rolled Ti-Zr-Ta series alloy is secondarily heated to 890-910 DEG C, kept for 100-120 seconds, and then subjected to secondary quenching to obtain an annealed Ti-Zr-Ta series alloy with heterogeneous structure. The high-temperature asynchronous rolling and short-time annealing process can increase the room temperature plasticity of the Ti-Zr-Ta series alloy by 1.5-2.5 times on the basis of stabilizing the strength of the Ti-Zr-Ta series alloy, and the overall process operation is simple, efficient, and has good practical application potential.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of metal material processing, in particular to a method for regulating high plasticity heterogeneous structure by asymmetric rolling and coupling recrystallization. BACKGROUND

[0002] Refractory complex concentrated alloys (RCCAs) have broad application prospects in extreme service environments such as aerospace, nuclear industry and high-temperature chemical equipment due to their excellent strength, wear resistance and radiation resistance. However, these alloys composed of high-melting-point elements such as Ti, Zr and Ta usually have body-centered cubic (BCC) structure, and are generally lack of room temperature ductility due to their intrinsic properties. This inherent low plasticity leads to brittle fracture during room temperature processing and use, making it difficult to fully utilize the excellent strength potential of the alloy, which greatly restricts the engineering promotion and application of such high-performance alloys.

[0003] To improve the plasticity of refractory alloys, existing technologies mainly focus on composition optimization and thermal mechanical treatment. For example, patent CN117248147A discloses a method of forming a lanthanum-rich phase by doping rare earth lanthanum elements to improve the strength and plasticity of refractory alloys; patent CN115404385A discloses a method of preparing a dendritic crystal and uniform structure ingot by precise composition ratio of Ti-V-Nb-Hf-W refractory alloy, and then using uniform rolling and recrystallization annealing to optimize the combination of strength and plasticity. However, the above traditional methods still face significant bottlenecks: cold rolling is prone to cracking and cannot be effectively deformed; while hot rolling can improve plastic deformation ability, but severe oxidation at high temperature is difficult to avoid, and neither uniform rolling nor conventional heat treatment can effectively reconcile the inherent contradiction between strength and plasticity at the microstructure level, making it difficult to significantly improve room temperature ductility while maintaining high strength characteristics.

[0004] To address the strength-plasticity contradiction, patent CN115976349A proposes a method of regulating heterogeneous grain structure by cold rolling and annealing, but it is only applicable to FCC structure alloys and is accompanied by significant strength loss after recrystallization annealing. Asynchronous rolling (asynchronous rolling or differential speed rolling) as a potential solution can introduce non-continuous shear strain in the material by using different roller speeds, inducing anisotropic strain field and dislocation density, providing the possibility of constructing heterogeneous structure. However, existing asynchronous rolling techniques only focus on grain refinement or flatness control of tantalum / zirconium alloys, such as patents CN114231870A and CN119753550A, which disclose asynchronous rolling processes only limited to room temperature cold rolling and do not involve active regulation of heterogeneous structure, nor do they lack research on the adaptability of heterogeneous processes for Ti-Zr-Ta alloys.

[0005] Therefore, in summary, it is urgent to develop a feasible process that can break through the limitations of the prior art, activate multiple strengthening and plasticizing mechanisms by coupling asymmetric rolling deformation and refined recrystallization parameters, and synergistically control heterogeneous structures, thereby solving the practical engineering application problem that the strength and plasticity of Ti-Zr-Ta series alloys are difficult to balance. SUMMARY

[0006] Therefore, the present application provides a method for metal asymmetric rolling coupled with recrystallization to regulate high plasticity heterogeneous structure, which solves the problem of synergistic improvement of strength and plasticity of Ti-Zr-Ta series alloys at room temperature by designing high-temperature asynchronous rolling, recrystallization annealing and related cooling process parameters.

[0007] To achieve the above object, the technical scheme adopted by the present application is as follows:

[0008] A method for metal asymmetric rolling coupled with recrystallization to regulate high plasticity heterogeneous structure, for Ti-Zr-Ta series alloys with a Ti atomic percentage of 33.3% to 53.3%, specifically comprising the following steps:

[0009] S1, heating the as-cast Ti-Zr-Ta series alloy to 890-910 DEG C for 1-2 h;

[0010] S2, differentially rolling the as-cast Ti-Zr-Ta series alloy after heat preservation by an asynchronous rolling mill, and then primary quenching to obtain a rolled Ti-Zr-Ta series alloy;

[0011] S3, secondary heating the rolled Ti-Zr-Ta series alloy to 890-910 DEG C, and then secondary quenching after 100-120 s of heat preservation to obtain an annealed Ti-Zr-Ta series alloy with heterogeneous structure.

[0012] Further, the speed ratio of the upper roller to the lower roller of the differential rolling is 2-4.

[0013] Further, the speed of the lower roller of the differential rolling is 6-10 rpm / min.

[0014] Further, the differential rolling is set to 3-5 passes, and the rolling reduction rate of each pass is 25-50%, and the total reduction rate is not less than 75%.

[0015] Further, the as-cast Ti-Zr-Ta series alloy is uniformly coated with an antioxidant coating of 0.3-0.8 mm thick.

[0016] Further, the cooling medium for the primary quenching and the secondary quenching is water, and the cooling rate is not less than 100 DEG C / s.

[0017] Furthermore, the secondary heating is performed by placing the rolled Ti-Zr-Ta alloy in a vacuum or argon quartz tube; when the heating device reaches the set temperature, the rolled Ti-Zr-Ta alloy is placed in a furnace for heating, and the insulation timer starts 10s to 15s after the heating device reaches the set temperature again.

[0018] Furthermore, during the differential rolling process, the rolling temperature is controlled to be 800°C to 900°C.

[0019] Furthermore, the heterogeneous structure includes a rolling deformation region and an annealing recrystallization region, wherein the volume fraction of the annealing recrystallization region is 50% to 80%.

[0020] Furthermore, the yield strength of the annealed Ti-Zr-Ta alloy with a heterogeneous structure is not less than 950 MPa, and the elongation is not less than 7%.

[0021] The beneficial effects of the present invention are:

[0022] 1) This invention utilizes a high-temperature differential rolling process for refractory alloys. By regulating the speed ratio of the upper and lower rollers, shear strain is introduced, significantly increasing the total equivalent strain and significantly increasing the stored energy and dislocation density in the rolled plate. Compared to conventional uniform rolling, differential rolling can introduce greater deformation at the same reduction rate, providing more nucleation sites for the subsequent recrystallization process.

[0023] 2) The present invention achieves a partially recrystallized microstructure through a short annealing treatment at 890°C to 910°C for 100 to 120 seconds. As the rotational speed ratio increases, the degree of recrystallization increases, while the size of the recrystallized grains decreases. This partially recrystallized, heterogeneous microstructure retains a certain amount of deformed structure to maintain strength while also improving the alloy's plasticity through the formation of recrystallized grains.

[0024] 3) Ti2ZrTa treated by the method of the present invention 0.75 The alloy can achieve a more than two-fold increase in tensile plasticity while maintaining high strength at a rotational speed ratio of 2 to 4. This excellent match between strength and plasticity effectively resolves the inverse contradiction between strength and plasticity that is difficult to overcome with traditional heat treatment methods.

[0025] 4) The process of combining high-temperature differential rolling with partial recrystallization annealing proposed in the present invention is simple to operate and highly efficient, without the need for complex composition design and long-term heat treatment. It provides a new approach to optimize the mechanical properties of refractory alloys and has great application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Various other advantages and benefits will become apparent to those of ordinary skill in the art, upon reading the following detailed description of the preferred embodiments with reference made to the accompanying drawings. The drawings provided herein are for illustrative purposes only and, therefore, should not be considered to be limiting in any way. For a better understanding of these implementations, please refer to the preferred embodiments described in greater detail by referring to the drawings wherein:

[0027] Figure 1 Ti2ZrTa in different processes 0.75 EBSD maps of the alloy, wherein: (a) is Comparative Example 1; (b) is Example 1; (c) is Example 2; (d) is a KAM statistical map;

[0028] Figure 2 Ti2ZrTa in different processes 0.75 EBSD maps of the alloy, wherein: (a) is Comparative Example 1; (b) is Example 1; (c) is Example 2; (d) is a recrystallized grain statistical map of Comparative Example 1; (e) is a recrystallized grain statistical map of Example 1; (f) is a recrystallized grain statistical map of Example 2;

[0029] Figure 3 Ti2ZrTa in different processes 0.75 Tensile curves of the alloy at room temperature. DETAILED DESCRIPTION

[0030] The present application can be further implemented or applied by different specific embodiments, and the details in the specification can be modified or changed based on different views and applications without departing from the spirit of the present application. The drawings are only used for illustrative purposes, and the representation is only a schematic diagram, not a physical diagram, and should not be considered as a limitation of the present application; for better illustration of the embodiments of the present application, it is understandable that some known structures or steps and their descriptions in the drawings can be omitted for those skilled in the art.

[0031] A method for regulating high plasticity heterogeneous structure by asymmetric rolling coupling recrystallization of metal, which is suitable for Ti-Zr-Ta alloy, specifically comprising the following steps:

[0032] S1, the as-cast Ti-Zr-Ta alloy is initially heated to 890-910°C and kept for 1-2h. This step is used to homogenize the Ti-Zr-Ta alloy structure on the one hand, and also to prepare for the subsequent hot rolling process, therefore, the initial heating method has less effect on the final alloy performance, and furnace heating or warm entry can be selected.

[0033] In order to explore the effect of temperature on the microstructure of the Ti-Zr-Ta alloy, a detailed thermal simulation experiment is carried out, and the results show that excessively high heating temperature and excessively long holding time will exacerbate grain coarsening and affect the performance of the alloy, and excessively low heating temperature will not only increase the deformation resistance, but also affect the phase composition. The experimental results show that heating below 800 DEG C will promote the Ti-Zr-Ta alloy to change from single-phase BCC crystal structure to dual-phase BCC structure, which will significantly increase the brittleness. Therefore, the rolling and heat treatment process of the Ti-Zr-Ta alloy in the application are carried out at a temperature above 800 DEG C. In addition, considering the continuity of different processes, the initial heating temperature is set to 890 DEG C to 910 DEG C.

[0034] S2, the as-cast Ti-Zr-Ta alloy after holding is subjected to multi-pass differential rolling by an asynchronous rolling mill, the rolling temperature is controlled in the range of 800 DEG C to 900 DEG C, and the rolled Ti-Zr-Ta alloy is obtained by primary quenching after rolling through cooling water. The core feature of asynchronous rolling is that the linear speeds of the upper and lower work rolls of the rolling mill are different, which can cause significant shear strain of the metal in the deformation zone, and then affect the rolled structure. Based on the characteristics of the Ti-Zr-Ta alloy, the lower roller speed in the application is controlled in the range of 6 rpm / min to 10 rpm / min, and high-speed ratio is used for rolling, and the speed ratio of the upper and lower rollers is set to 2 to 4, so as to significantly increase the total equivalent strain, and then greatly increase the stored energy and dislocation density in the rolled plate.

[0035] Different from the cold rolling method mainly dominated by work hardening commonly used in traditional refractory alloys, the rolling method in the application is high-temperature hot rolling, and not only work hardening but also dynamic recrystallization occurs during rolling, and the synergistic effect of asynchronous rolling will make the grain size of the obtained Ti-Zr-Ta alloy smaller and more uniform. Compared with cold rolling, under high-temperature conditions, the deformation capacity of the Ti-Zr-Ta alloy is better, which can not only bear higher speed ratio and larger deformation, but also reduce the degree of wear of the roller. Therefore, in the application, the rolling pass is set to 2 to 4, and the rolling reduction rate of each pass is 25% to 50%, and the total reduction rate is not less than 75%.

[0036] S3, the as-rolled Ti-Zr-Ta alloy is secondarily heated to 890-910℃, and after holding for 100-120s, secondarily quenched to obtain the annealed Ti-Zr-Ta alloy with heterogeneous structure. The secondary heating mode is to warm up and then enter the furnace, that is, when the heating equipment reaches the set temperature of 890-910℃, the as-rolled Ti-Zr-Ta alloy is heated in the furnace. Since the grain size is abnormally sensitive to the annealing temperature and holding time, it should be strictly controlled. When the heating equipment reaches the set temperature of 890-910℃ again for 10-15s, the holding time of 100-120s is started immediately to ensure that the heterogeneous structure with excellent comprehensive mechanical properties can be finally controlled in the Ti-Zr-Ta alloy.

[0037] The annealed Ti-Zr-Ta alloy obtained by the above method has a heterogeneous microstructure, and the heterogeneous structure includes a rolling deformation region and an annealing recrystallization region, wherein the volume fraction of the annealing recrystallization region is 50%-80%. The mechanical results show that the yield strength of the Ti-Zr-Ta alloy with the heterogeneous structure is not less than 950MPa, and the elongation is not less than 7%. Compared with the conventional rolling process, the room temperature plasticity is significantly improved, and the strength is almost not lost. This is because the recrystallization degree is improved, which can significantly reduce the dislocation density of the hot-rolled alloy, and the stored energy is released, thereby improving the plasticity of the alloy. The heterogeneous microstructure will produce a strain gradient on the side of the recrystallized grain at the interface between the soft and hard regions during deformation, resulting in the accumulation of geometrically necessary dislocations in the recrystallized grain at the interface between the soft and hard regions, forming a long-range stress field, i.e. the so-called back stress. The back stress strengthening effect can significantly improve the yield strength of the alloy, which is the main reason for maintaining high strength at a higher recrystallization degree.

[0038] In addition, in order to retain the fine structure formed after rolling as much as possible and avoid the grain coarsening and recovery after annealing, in the method of the present application, the cooling rate of the primary quenching and the secondary quenching is set to be not less than 100℃ / s.

[0039] The specific embodiments of the present application will be further described in detail below in combination with the accompanying drawings Figures 1-3 , examples and comparative examples. In order to reduce experimental errors, the examples and comparative examples all use Ti2ZrTa 0.75 and TiZrTa alloy ingots prepared by vacuum arc melting with a size of 10mmx10mmx70mm. Among them, the purity of the raw materials Ti, Zr and Ta in the Ti2ZrTa 0.75 and TiZrTa alloy ingots is more than 99.9%, and the ingot is remelted at least 6 times to make the chemical elements uniformly distributed. The Ti atomic percentage of Ti2ZrTa 0.75 is 53.3%, and the Ti atomic percentage of TiZrTa is 33.3%.

[0040] Example 1

[0041] Ti2ZrTa alloy with a size of 8mm x 8mm x 65mm was cut from an ingot 0.75 The sample was uniformly coated with an oxidation-resistant coating of 0.5mm in thickness on its surface to prevent high-temperature oxidation. Subsequently, the sample was heated to 890°C in a box-type resistance furnace and held for 1 hour to homogenize the structure and prepare for subsequent processes.

[0042] The cast Ti2ZrTa 0.75 The sample was differentially rolled on an asynchronous rolling mill, with the lower roller set at a speed of 8rpm / min, and the speed ratio of the upper and lower rollers was controlled to be 2 by adjusting the speed of the upper roller, i.e., the speed of the upper roller was 16rpm / min. Under this speed ratio, the cast Ti2ZrTa 0.75 alloy was rolled for 3 passes, with a reduction of about 2mm per pass, and the final thickness was reduced to 2mm, with a total reduction rate of about 75%. After rolling, the sample was subjected to primary water quenching.

[0043] The sample after primary water quenching was placed in a high-purity argon quartz tube for sealing treatment to avoid severe oxidation and loss of the sample during subsequent annealing. The box-type resistance furnace was heated to 890°C at a rate of 10°C / min, and after the temperature of the furnace reached 890°C again, the sealed rolled Ti2ZrTa 0.75 sample was placed in the furnace for heating. After the temperature of the box-type resistance furnace reached 890°C again, the sample was taken out after 120s of holding time, and subjected to secondary water quenching.

[0044] Example 2

[0045] Compared with Example 1, in Example 2, the primary heating temperature was 910°C, the speed of the lower roller was 8rpm / min, the speed of the upper roller was 32rpm / min, the speed ratio was 4, the secondary heating temperature was 910°C, the holding time was 100s, and the other process parameters were unchanged.

[0046] Example 3

[0047] Compared with Example 1, in Example 3, the sample was an equiatomic TiZrTa alloy, and the other process parameters were unchanged. The yield strength of the TiZrTa alloy reached more than 955Mpa, and the elongation reached more than 7.3%.

[0048] Comparative Example 1

[0049] Compared with Example 1, in Comparative Example 1, synchronous rolling was used, i.e., the speed of the upper and lower rollers was set to 8rpm / min, and the other process parameters were unchanged.

[0050] Comparative Example 2

[0051] In Comparative Example 2, the initial heating temperature was 1000 °C, and other process parameters were unchanged compared with Example 1.

[0052] Comparative Example 3

[0053] In Comparative Example 3, the secondary heating holding time was set to 300 s, and other process parameters were unchanged compared with Example 1.

[0054] Comparative Example 4

[0055] In Comparative Example 4, the secondary heating temperature was set to 1000 °C, and other process parameters were unchanged compared with Example 1.

[0056] The examples and comparative examples were analyzed in combination with the drawings. As shown in Figure 1 (a-c), the as-rolled Ti2ZrTa 0.75 The microstructure of the samples was highly elongated deformed grains along the rolling direction, and small equiaxed grains were observed at the deformed grain boundaries, indicating that dynamic recrystallization occurred during hot rolling, and new grains preferentially nucleated at the deformed grain boundaries, which is a typical feature of discontinuous dynamic recrystallization. Compared with Comparative Example 1, the volume fraction of the annealing recrystallization region increased in Examples 1 and 2, especially in Example 2. Statistical data showed that the proportion of high-angle grain boundaries increased from 25% (Comparative Example 1) to 30% (Example 2) with the increase of the speed ratio. This is because the increased shear strain introduced by different speed rolling increases the total equivalent strain, which is more conducive to activating dynamic phase transformation (dynamic recovery and dynamic recrystallization) and increasing the nucleation rate. The distribution of dislocation density in different grains can be represented by local misorientation, as shown in Figure 1 (d), with the increase of the speed ratio, the local misorientation increased significantly, which means that high-speed differential rolling caused extensive dislocation multiplication and slip.

[0057] As shown in Figure 2 (d), the differential rolling and partial recrystallization annealing made the Ti2ZrTa 0.75The sample formed a heterogeneous microstructure including a rolling deformation area and an annealing recrystallization area. The microstructure statistics showed that the volume fraction of the annealing recrystallization area in Comparative Example 1 was 45.67%. In Comparative Example 2, due to the high initial heating temperature, dynamic recrystallization consumed a lot of storage energy, and recrystallization was quite unnoticeable during the secondary heating process. The volume fraction of the annealing recrystallization area was 23.4%, and there was still significant work hardening, and the plastic recovery was limited. Comparative Examples 3 and 4 underwent complete recrystallization due to the long secondary heating holding time and the high secondary heating temperature. The microstructure lost the characteristics of the heterogeneous structure, resulting in a decrease in strength. The annealing recrystallization area of ​​Example 1 and Example 2 increased to 55.59% and 66.78% respectively. The shear strain introduced by differential rolling increased the dislocation density and distortion storage energy of the alloy, resulting in an increase in the recrystallization driving force and nucleation rate, which increased the volume fraction of the annealing recrystallization area compared to Comparative Example 1. The increase in the degree of recrystallization weakens the work hardening to improve plasticity. The heterogeneous microstructure composed of soft recrystallized areas and hard deformed grains has a significant back stress strengthening effect, which is conducive to maintaining high strength.

[0058] like Figure 3 As shown, the yield strength of the sample in Example 1 is 960 MPa, but its plasticity is limited, only 5.5%; the elongation of Example 2 is only 2.4%; the yield strength of Example 3 is 840 MPa, and the elongation is 12.1%; the yield strength of Example 4 is 905 MPa, and the elongation is 10.8%. The elongation of the sample in Example 1 is 8.9%, which is about 1.6 times higher than that in Example 1, and the yield strength is 957 MPa, with a fluctuation range of only about 0.3%. Compared with Examples 1 and 2, the plasticity of the sample in Example 2 with a speed ratio of 4 is more significantly improved, and its elongation is increased to 13.6%, which is about 2.5 times that of Example 1. At the same time, its strength is also synergistically optimized compared to Examples 3 and 4, and the yield strength is increased to 984 MPa. The results of the above examples show that the method of the present invention can significantly optimize the room temperature plasticity of Ti-Zr-Ta alloys without losing strength, and has good application prospects.

[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope defined by the claims of the present invention.

Claims

1. A method for regulating high plasticity heterogeneous structures by coupling metal asymmetric rolling with recrystallization, characterized in that: For Ti-Zr-Ta alloys with a Ti atomic percentage of 33.3% to 53.3%, the method specifically includes the following steps: S1. Initially heat the cast Ti-Zr-Ta alloy to 890°C~910°C and keep it at this temperature for 1h~2h; S2. performing multi-pass differential rolling on the as-cast Ti-Zr-Ta alloy after holding by an asynchronous rolling mill, and performing primary quenching after the differential rolling to obtain a rolled Ti-Zr-Ta alloy; S3. The rolled Ti-Zr-Ta alloy is reheated to 890° C. to 910° C., kept at this temperature for 100 s to 120 s, and then subjected to secondary quenching to obtain an annealed Ti-Zr-Ta alloy with a heterogeneous structure.

2. The method for regulating high plasticity heterostructure by metal asymmetric rolling coupled with recrystallization according to claim 1, characterized in that: The speed ratio of the upper roller and the lower roller in the differential rolling is 2-4.

3. The method for regulating high plasticity heterostructure by coupling metal asymmetric rolling with recrystallization according to claim 1, characterized in that: The rotation speed of the lower roller of the differential rolling is 6 rpm / min to 10 rpm / min.

4. The method for regulating high plasticity heterostructure by coupling metal asymmetric rolling with recrystallization according to claim 1, characterized in that: The differential rolling is performed in 3 to 5 passes, with a rolling reduction rate of 25% to 50% in each pass, and a total rolling reduction rate of not less than 75%.

5. The method for regulating high plasticity heterostructure by coupling metal asymmetric rolling with recrystallization according to claim 1, characterized in that: The surface of the cast Ti-Zr-Ta alloy is evenly coated with an anti-oxidation coating with a thickness of 0.3 mm to 0.8 mm.

6. The method for regulating high plasticity heterostructure by coupling metal asymmetric rolling with recrystallization according to claim 1, characterized in that: The cooling medium for the primary quenching and the secondary quenching is water, and the cooling rate is not less than 100°C / s.

7. The method for regulating high plasticity heterostructure by coupling metal asymmetric rolling with recrystallization according to claim 1, characterized in that: The secondary heating is performed by placing the rolled Ti-Zr-Ta alloy in a vacuum or argon quartz tube; when the heating device reaches the set temperature, the rolled Ti-Zr-Ta alloy is placed in a furnace for heating, and when the heating device reaches the set temperature again, 10s to 15s later, the heat preservation timer is started.

8. The method for regulating high plasticity heterostructure by coupling metal asymmetric rolling with recrystallization according to claim 1, characterized in that: During the differential rolling process, the rolling temperature is controlled to be 800° C. to 900° C.

9. The method for regulating high plasticity heterostructure by coupling metal asymmetric rolling with recrystallization according to claim 1, characterized in that: The heterogeneous structure includes a rolling deformation region and an annealing recrystallization region, wherein the volume fraction of the annealing recrystallization region is 50% to 80%.

10. The method for regulating high plasticity heterostructure by coupling metal asymmetric rolling with recrystallization according to claim 1, characterized in that: The yield strength of the annealed Ti-Zr-Ta alloy with a heterogeneous structure is not less than 950 MPa, and the elongation is not less than 7%.

Citation Information

Patent Citations

  • Tantalum alloy rolling deformation composite self-resistance heating annealing rapid fine grain preparation method

    CN114231870A

  • Zirconium alloy ultrathin plate for nuclear fuel assembly grillwork and preparation method of zirconium alloy ultrathin plate

    CN119753550A

  • Method for preparing ultra-thin strip by adopting TC4 titanium alloy EB ingot

    CN117019914A

  • Preparation method of heterostructure titanium alloy with strength not limited by alpha-phase content

    CN118256836A